The Concept of Kufr in Leader Verses : A Comparative Interpretation Study - Muhammad, Muhammad; Barmawi, Mahral (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Group existence and orientation is highly determined by the leader, whether they are brought to the goodness, wealth and prosperity or even to destruction. Therevore, it becomes a responsibility for the whole of people ton be selective and careful in electing a leader. Leader is a main character who has uphold justive and the principle of equality for all communities which has been taught by the newspaper and a leader is the one who holds the god mandate as well. The main leardership principles are justive and waithy for every people to whom he leads. On every leader election in the rest of the year especially in Indonesia the phenomenon of political conflict is often happned. Whereas it takes the name of religion and ideology. There are several groups voiced ang tald that Islam forbid moeslem to choose kafir or non moeslem leader. A number of newspaper verses are used as theorem to lagetimate the issue and designed the propaganda verses. These verses can be are the meaning relates to leadership in Kuran there are about ten verses which almost have the same meaning and understood as the leadership verses the verses Al?- Imr?n 118, 28, An-Nis?' 144, 89, 139, AlMaidah, 51, 57 and 81 and Mumtahanah 1. In the verses that are mentioned above, at least one word that a lot of people take it as leadership verse.